2018
DOI: 10.1289/ehp2045
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Air Pollution Exposure, Genome-wide DNA Methylation and Lung Function in the LifeLines Cohort Study

Abstract: Background:Long-term air pollution exposure is negatively associated with lung function, yet the mechanisms underlying this association are not fully clear. Differential DNA methylation may explain this association.Objectives:Our main aim was to study the association between long-term air pollution exposure and DNA methylation.Methods:We performed a genome-wide methylation study using robust linear regression models in 1,017 subjects from the LifeLines cohort study to analyze the association between exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 65 publications
5
57
1
Order By: Relevance
“…We initially identified 19 manuscripts (2–10,27–36) based on the search terms and after reading the full manuscripts we finally selected 9 studies (210). We selected 12 CpGs showing differential methylation in relation to PM 2.5 from the only manuscript that corrected for Bonferroni criteria (9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We initially identified 19 manuscripts (2–10,27–36) based on the search terms and after reading the full manuscripts we finally selected 9 studies (210). We selected 12 CpGs showing differential methylation in relation to PM 2.5 from the only manuscript that corrected for Bonferroni criteria (9).…”
Section: Resultsmentioning
confidence: 99%
“…The most studied epigenetic mechanism is DNA methylation, which is heritable but can also be modified by life-style and environmental factors. Recently, several studies have analyzed the association between air pollution and DNA methylation using a genome-wide approach, and have reported numerous loci showing differential methylation related to this exposure (210). The aims of this study were both to identify new genomic loci showing differential methylation associated with long-term exposure to air pollution in a population-based study in Spain and to replicate loci previously reported in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, given the large distinction in the physical properties of these two carbon nanoparticles (CNPs) it is inappropriate to characterize the toxicity of airborne BC-containing CNPs in in vivo or in vitro studies using industrial CB. Furthermore, as evidenced by accumulating epidemiology and laboratory studies, short-or long-term exposure to fine PM or nanosized materials would induce remarkable changes in the methylation status of whole genome or specific genes in cells or organisms (de F C Lichtenfels et al, 2018;De Nys et al, 2018). Similar links were observed between PM-containing BC exposure and DNA methylation.…”
mentioning
confidence: 76%
“…Furthermore, as evidenced by accumulating epidemiology and laboratory studies, short‐ or long‐term exposure to fine PM or nanosized materials would induce remarkable changes in the methylation status of whole genome or specific genes in cells or organisms (de F C Lichtenfels et al, ; De Nys et al, ). Similar links were observed between PM‐containing BC exposure and DNA methylation.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is currently the most widely investigated epigenetic mechanism and occurs through the addition of a methyl group to a cytosine-guanine dinucleotide (CpG site) [9,10]. Alteration in DNA methylation may be induced by exposure to air pollution, thus altering gene expression patterns [11].…”
mentioning
confidence: 99%